Digital Multidomain Lifestyle Intervention for Community-Dwelling Older Adults: A Mixed Methods Evaluation - Mattli, Renato; Weber, Manuel; Raab, Anja Maria; Haas, Karin; Vorster, Albrecht; Schmitt, Kai-Uwe (International Journal of Public Health, 2025)
Objectives: As life expectancy rises at a faster rate than healthy life expectancy, there is a global need for scalable and cost-effective interventions that enhance the health-related quality of life (HRQoL) of older adults. This study aimed to examine the use and usability of a 12-week digital multidomain lifestyle intervention in community-dwelling older adults aged 65 years and above. Methods: The intervention was delivered through a mobile application (app) and focused on physical activity, nutrition, sleep and mindfulness/relaxation. We used a cross-over interventional study design and a mixed methods sequential explanatory approach. We delivered online questionnaires before and after the intervention, collected app usage data and conducted semi-structured interviews. Results: One hundred eight older adults participated in the study. Fifty-six percent of participants completed the twelve weeks intervention. Both overall satisfaction and the app's usability received high ratings. Important dimensions of HRQoL showed a statistically significant change from pre- to post-intervention. Conclusions: A digital multidomain lifestyle intervention can be well accepted and perceived by community-dwelling older adults and has the potential to improve HRQoL.